Micropropagation of Stevia Rebaudiana and Tylophora Indica and Extraction of Secondary Metabolites - Kaur, Harmanjit (My University, 2012)
A successful plant propagation system through multiple shoot proliferation and de novo adventitious shoot formation directly from different explants and through intervening callus phase was achieved in Stevia rebaudiana. Tylophora indica exhibited high degree of propensity for plant regeneration through different methods of micropropagation viz. forced axillary branching, de novo adventitious shoot formation and somatic embryogenesis. Comparative analysis of metabolites in in vitro regenerated plants and in vivo plants at different age intervals was made to quantify the amount of metabolites yielded by plants at different phases of growth. Suspension cultures yielded higher amounts of secondary metabolites as compared to callus cultures but these were less than the one obtained from in vitro regenerated plants. The results of the present work indicate that in vitro raised plants of S. rebaudiana and T. indica respectively may be ideal candidates for further research in the natural plant based pharmaceutical products.
Keywords: Tylophora indica; Stevia rebaudiana; micropropagation; secondary metabolites; medicinal plants